2016
DOI: 10.1188/16.cjon.385-390
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a Question Prompt List on an Inpatient Oncology Unit to Increase Prognostic Awareness

Abstract: An increase was seen in the percentage of patients with active DNR orders and in hospice referrals after a discussion aid was included in admission packets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…An increase in do not resuscitate (DNR) orders and hospice referrals was seen with this intervention. 17 Giving patients an instructive prompt and control over which prognostic questions to ask has the added benefit of giving them a sense of agency that is invaluable in their care.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in do not resuscitate (DNR) orders and hospice referrals was seen with this intervention. 17 Giving patients an instructive prompt and control over which prognostic questions to ask has the added benefit of giving them a sense of agency that is invaluable in their care.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, patients reported the QPL to be useful, such that it could be beneficial for the caregivers to engage in question‐asking, 31,32 it was a good communication tool which organized and prompted patients to ask questions during the consultation, 38,42 helped patients address critical questions related to end‐of‐life, and reduced the burden of comprehending excessive information 32,43 . Similarly, McLawhorn et al 44 reported that the use of QPL increased the number of do‐not‐resuscitate orders and hospice referrals. During the consultation, it was observed that patients using the QPL did ask more questions, 31 were able to address important concerns they had, 45 and engaged in a meaningful discussion with their physician, 27,29 and the time taken for the medical consultation was not impacted 29,31 .…”
Section: Methodsmentioning
confidence: 99%
“…Given these issues identified that were associated with the Iranian women's making decisions about breast cancer treatment, we asked the healthcare team to identify potential questions that could be added to the QPL to enable patients to participate in shared decision-making. Existing evidence and other QPLs were considered for developing the QPLs (chemotherapy-related QPL and radiotherapyrelated QPL) to be used in the proposed study (18,(20)(21)(22)).…”
Section: Interventionmentioning
confidence: 99%